2018
DOI: 10.1016/j.apradiso.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

How mobile is tritiated water through unsaturated cement-based materials? New insights from two complementary approaches

Abstract: This work presents a novel approach to study tritiated water (HTO) diffusion through unsaturated cement-based materials (hardened CEM V/A cement pastes). The diffusion studies were performed under hydric conditions covering those that can prevail in near-surface disposal facilities for short-lived nuclear waste. In order to investigate the required large range of suction, two complementary techniques were developed. The first technique was based on a through-diffusion method where suction (up to 9 MPa) was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Diffusion experiments have shown that anion diffusion is more strongly reduced than cation diffusion in the presence of water unsaturated conditions. Numerous processes were put forward to explain this observation, including differences in diffusion pathway disruptions among cations, anions, and neutral molecules. Our study emphasizes that mechanisms taking place at the surface, such as formation and immobilization of ion pairs, may also be partly responsible for the observed differences between anion and cation diffusion property evolution with desaturation. As for water diffusion, our study corroborates the fact that a limited desaturation is not responsible for a decrease of water molecules self-diffusion coefficient.…”
Section: Resultsmentioning
confidence: 77%
“…Diffusion experiments have shown that anion diffusion is more strongly reduced than cation diffusion in the presence of water unsaturated conditions. Numerous processes were put forward to explain this observation, including differences in diffusion pathway disruptions among cations, anions, and neutral molecules. Our study emphasizes that mechanisms taking place at the surface, such as formation and immobilization of ion pairs, may also be partly responsible for the observed differences between anion and cation diffusion property evolution with desaturation. As for water diffusion, our study corroborates the fact that a limited desaturation is not responsible for a decrease of water molecules self-diffusion coefficient.…”
Section: Resultsmentioning
confidence: 77%
“…This exchange is assumed to be instantaneous, reversible and without significant fractionation between the different isotopes of the water molecules, as demonstrated by Savoye et al (2018) for HTO.…”
Section: Application Of a Double-diffusion Model In Both Vapor And Li...mentioning
confidence: 99%
“…Similar to seismic performance and fire resistance, the dynamic mechanical properties are an important indicator of the macro performance of green cement matrix composite structures [18][19][20][21][22]. Tran et al [23] investigated the dynamic mechanical properties of two typical green composites, i.e., cement matrix regeneration composite and alkaline-activated material, studied how the graphene oxide content enhances the macro dynamic mechanical properties of cement matrix regeneration composite, analyzed the influence of different renewable rubber replacement ratios on the fluidity and static mechanical properties of alkaline-activated material, and evaluated the ecological and economic performance of the materials through mix ratio optimization.…”
Section: Introductionmentioning
confidence: 99%